Indexical signs and artistic, political and historical complexity (2020)
Artists, political scientists and art historians share with other professionals the challenge of apprehending and comprehending the complexity of the realities they address in their work. The co‐authors of our article coincide in the prominence they give to disturbing indexical signs (i.e., indications and traces of trauma and normalization in people, in political processes and works of art), as keys of interpretation and problematizing at the basis of their art works, their social work and their historic and political research. They address the challenges and questions they face when interacting with the multiple dimensions inherent to the complex human behaviours, theoretical concepts and artistic statements on which they focus. Finally, they discuss possible aesthetic, ethical and philosophical implications of their proposals and perspectives.